MENTORING TRAINING 'CONTINUE TO STUDY WITH SCHOLARSHIPS' IN SUPPORTING THE IMPROVEMENT OF THE COMPETITIVENESS OF THE PEOPLE OF LAMPUNG - Zainal, Anna Gustina; Windah, Andi; Firdaus, Feri; Suciska, Wulan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Human Development Index (HDI) in Lampung Province has increased from 70.45 in 2022 to 71.15 in 2023. However, Lampung's HDI is still the lowest in Sumatra. One of the factors causing this is the low Average Length of School (RLS) which is only 8.29 years, the second lowest in Sumatra. The low RLS is due to the low public interest in higher education. Economic factors and lack of understanding of the importance of higher education are the main causes. The Service Team from the Department of Communication Sciences then provides education, motivation, and mentoring to parents and high school students in Lampung to increase their interest in higher education with scholarships. Effective persuasive communication strategies are used to change people's perceptions of the cost of higher education and open up their insights into available scholarship opportunities. Before the training began, a pre-test was conducted to measure the level of participants' initial understanding of higher education and scholarships. The results of the pre-test showed that most participants had a limited understanding of higher education opportunities and accessible scholarship resources. After a series of training sessions that included educational, motivational, and mentoring sessions with a persuasive communication approach, a post-test was conducted to measure the impact of the activity. The results of the post-test showed a significant improvement. In addition to increasing knowledge, the participants also revealed a change in attitudes towards higher education. Parents, who had previously been worried about the cost of education, showed greater interest in supporting their children to pursue higher education through the scholarship pathway. The students who took part in the training also showed greater enthusiasm and motivation to continue their education. Overall, this service activity has proven successful in achieving its goal, which is to increase public awareness and interest, especially in Lampung Province, to continue higher education through scholarships.